EFEKTIFITAS ASUHAN KEPERAWATAN KELUARGA TERHADAP PENINGKATAN SELF EFICACY IBU HAMIL DAN MENYUSUI DALAM PEMBERIAN ASI EKSLUSIF - Maria Ulfah (STIKes MERCUBAKTIJAYA, 2021)
Family is the main group in maintaining health, and is the main actor in providing care to its members who are giving exclusive breastfeeding. The strategy used is the approach of family and family supporters of ASI. This study aims to provide an overview of the application of ASI-supporting families in increasing self-efficacy. The design of this study was a case study of 10 families with pregnant women and / or nursing mothers taken through purposive sampling technique. The results showed that pregnant and nursing mothers need family support in improving self-efficacy and behavior in breastfeeding.